2022
DOI: 10.1007/s40120-022-00326-y
|View full text |Cite|
|
Sign up to set email alerts
|

Staging Disease Severity Using the Alzheimer’s Disease Composite Score (ADCOMS): A Retrospective Data Analysis

Abstract: Introduction: The Alzheimer's disease (AD) composite score (ADCOMS) has been shown to be a more sensitive measure of cognitive change in early AD (i.e., mild cognitive impairment [MCI] and mild AD) than commonly used measures. This study derived ADCOMS value

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…ADCOMS scores for each subject at each assessment time point were calculated from the constituent item scores extracted from several ADNI files (listed in the supplement preamble). The method for calculating ADCOMS is described comprehensively elsewhere 1,14 ; however, Figure 1 shows ADCOMS’ maximum contributions from each of the item responses, weighted by the relevant coefficient. All items have a cognitive or functional focus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ADCOMS scores for each subject at each assessment time point were calculated from the constituent item scores extracted from several ADNI files (listed in the supplement preamble). The method for calculating ADCOMS is described comprehensively elsewhere 1,14 ; however, Figure 1 shows ADCOMS’ maximum contributions from each of the item responses, weighted by the relevant coefficient. All items have a cognitive or functional focus.…”
Section: Methodsmentioning
confidence: 99%
“…ADCOMS scores for each subject at each assessment time point were calculated from the constituent item scores extracted from several ADNI files (listed in the supplement preamble). The method for calculating ADCOMS is described comprehensively elsewhere 1,14 ; however, Figure 1 The weighted sum of CN item scores will be less than for those with MCI, and only the most severe dementia cases will have the highest ADCOMS score. In its final form, the ADCOMS scale extends from 0 up to 1.97 as cognitive and functional severity increases.…”
Section: Adcoms Score Componentsmentioning
confidence: 99%
“…ADCOMS ADCOMS (range 0-1.97; higher scores indicate more severe impairment) is a statistically derived composite measure which consists of 12 clinically sensitive items from other clinical scales; the 6 CDR domains, 4 items from ADAS-Cog, and 2 items from the Mini-Mental State Examination (MMSE) [7,15]. This composite consists of cognitive and functional components of variable statistical weights [7]; scores typically range from 0.11 to < 0.31 in MCI and 0.31 to 0.77 in mild AD dementia [16]. Lecanemab slowed the worsening (i.e., increase) in baseline ADCOMS scores by 0.05 points (p < 0.001) at 18 months compared to placebo, reflecting 24% slowing of progression (Table 1).…”
Section: Adas-cog14mentioning
confidence: 99%
“…Numerical representation of the differences between AD stages. Monfared et al [81] calculated the range of Alzheimer's disease composite scores to assess the severity of the cognitive decline in patients. Sheng et al [82] made multiple classifications and concluded that the gap between late mild cognitive impairment and early mild cognitive impairment was small, whereas a greater difference exists between early and late MCI patients.…”
Section: Challenges In Researchmentioning
confidence: 99%